2016
DOI: 10.1159/000448844
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Exon-3-Deleted Growth Hormone Receptor on Pegvisomant-Treated Acromegaly: A Systematic Review and Meta-Analysis

Abstract: Background: The common exon 3 deletion polymorphism of the growth hormone receptor (d3-GHR) is associated with disease severity in acromegaly patients. The GHR antagonist pegvisomant (PEGV) is highly effective in treating severe acromegaly. Response to PEGV treatment seems to be influenced by d3-GHR and appears to be more responsive to PEGV, although available results remain conflicting. Objective: To assess the influence of d3-GHR on the responsiveness of acromegaly patients to PEGV by compiling the evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The increased intracellular signal transduction may increase the sensitivity to GH: GH-deficient children carried the d3-GHR have an increased growth velocity and a higher final height (44) when treated with recombinant human GH (rhGH). In adult GHD patients, d3-GHR influences positively also metabolic and bone effects of rhGH (17,45). On the other hand, d3-GHR polymorphism confers higher susceptibility to GH stimulation in patients with acromegaly and may negatively affect phenotypic presentation and long-term complications of the disease, as showed in bone metabolism (46).…”
Section: Discussionmentioning
confidence: 99%
“…The increased intracellular signal transduction may increase the sensitivity to GH: GH-deficient children carried the d3-GHR have an increased growth velocity and a higher final height (44) when treated with recombinant human GH (rhGH). In adult GHD patients, d3-GHR influences positively also metabolic and bone effects of rhGH (17,45). On the other hand, d3-GHR polymorphism confers higher susceptibility to GH stimulation in patients with acromegaly and may negatively affect phenotypic presentation and long-term complications of the disease, as showed in bone metabolism (46).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies previously reported about a GH receptor polymorphism lacking exon 3, which seemed to have an influence as well during PEGV dosing (21,22). However, more recent studies in larger acromegaly cohorts clearly state that this polymorphism has a clinical effect on neither the PEGV response nor the determination of the required PEGV dose (23,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…For pegvisomant, some predictors have been described like pre-treatment GH and IGF-I levels, age and BMI ( 67 ). Expression of exon3-deleted growth receptor has been proposed as a predictor of response to pegvisomant in some studies, although it has not been confirmed in larger series ( 68 , 69 ).…”
Section: Precision Medicine In the Treatment Of Acromegalymentioning
confidence: 98%